A finite element analysis of different pedicle screw placement strategies for treatment of Lenke 1 adolescent idiopathic scoliosis: which is better?. Issue 3 (17th February 2021) - Chen, Kai; Zhao, Jian; Zhao, Yunfei; Yang, Changwei; Li, Ming
Abstract: Objective: To simulate the process of curve correction with different strategies of pedicle screws placement, and then explore the ideal strategy. Materials and methods: A three-dimensional model was constructed using CT data from a Lenke 1 AIS patient for finite element analysis. Five screw-placement strategies were designed, including collocation of consecutive, interval and alternate screws instrumentation in convex or concave side. The whole surgical procedures of screw-placement strategies were simulated. And their influences in the curve correction as well as the biomechanics of the implants and implant–bone interface were analyzed. Results: The densities of pedicle screws were 100%, 79%, 64%, 57% and 50%, respectively. During curve correction, interval and alternate screws instrumentation demonstrated higher screws stress, while the higher rods and screw–rod interface was observed in consecutive screws instrumentation. When it referred to the interaction force between screws and vertebrae, a lower stress was observed in in consecutive screws instrumentation. After the fixation of rod at convex side, the maximum stress on screws in each strategy was observed in interval screws instrumentation. The higher stress of rods was observed in alternate screws instrumentation in both sides. However, the correction rate of each strategy was similar. Conclusion: There was little distinction on the curve correction rate in different screw-placement strategies. The screw-placement strategy with interval and alternate screws instrumentation has better biomechanics properties than others, except for higher maximum interaction force between screws and vertebrae.